The complete mitochondrial genome of Carpodacus pulcherrimus (Passeriformes: Fringillidae). Issue 3 (2nd July 2020) - Yang, Nan; Li, Feng-jun; Yang, Kong; Qiao, Lu; Yue, Bi-song
Abstract: The Himalayan Beautiful Rosefinch Carpodacus pulcherrimus, belongs to the family Fringillidae, distributed in central Himalayas from India (Himachal Pradesh) to southwest China and Bhutan. The conservation status of this species is least concern (LC) in IUCN. In this study, the complete mitogenome of C. pulcherrimus was determined. The mitogenome is a circular molecule of 16, 797 bp in length, containing 13 protein-coding genes, 2 ribosome RNA genes, 22 transfer RNA genes, and 1 non-coding region. We reconstructed a phylogenetic tree based on Bayesian inference for other 14 Fringillidae species. The new mitogenome data would provide useful information for application in conservation genetics and further clarify phylogenetic evolution of this species.